2020
DOI: 10.3389/fphar.2020.01150
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Hydrogen Sulfide Ameliorates Diabetic Myocardial Fibrosis by Inhibiting Cell Aging Through SIRT6/AMPK Autophagy

Abstract: Stress aging of myocardial cells participates in the mechanism of myocardial fibrosis (MF). Previous studies have shown that hydrogen sulfide (H 2 S) can improve MF, however the specific internal mechanism remains still unclear. Therefore, this study aims to explore whether H 2 S can improve myocardial cell aging induced by high glucose and myocardial fibrosis in diabetic rats by activating autophagy through SIRT6/AMPK. We observed that HG (high glucose, 33 mM) ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…With the further research on the improvement of diabetes by H 2 S regulating autophagy, it may provide a new strategy for the treatment of diabetes. Diabetic cardiomyopathy Activating autophagy through activating AMPK/mTOR signaling pathway [59] Diabetes-induced myocardial fibrosis Inhibiting autophagy via activating PI3K/AKT1 signaling pathway [63] Diabetes-induced myocardial fibrosis Suppressing myocardial cell senescence via activating autophagy through activating SIRT6/AMPK signaling pathway [66] High glucose-induced endothelial cell dysfunction Inhibiting autophagy via the Nrf2/ROS/AMPK signaling pathway [75] Diabetes-induced renal fibrosis Activating autophagy via inhibiting TGFβ1/NF-κB/AKT pathways [83] Diabetic dysfunctional vascular smooth muscle Inhibiting autophagy via suppressing the AMPK/mTOR pathway [92] Diabetic depression Promoting autophagy via activating BDNF/TrkB pathway [99]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the further research on the improvement of diabetes by H 2 S regulating autophagy, it may provide a new strategy for the treatment of diabetes. Diabetic cardiomyopathy Activating autophagy through activating AMPK/mTOR signaling pathway [59] Diabetes-induced myocardial fibrosis Inhibiting autophagy via activating PI3K/AKT1 signaling pathway [63] Diabetes-induced myocardial fibrosis Suppressing myocardial cell senescence via activating autophagy through activating SIRT6/AMPK signaling pathway [66] High glucose-induced endothelial cell dysfunction Inhibiting autophagy via the Nrf2/ROS/AMPK signaling pathway [75] Diabetes-induced renal fibrosis Activating autophagy via inhibiting TGFβ1/NF-κB/AKT pathways [83] Diabetic dysfunctional vascular smooth muscle Inhibiting autophagy via suppressing the AMPK/mTOR pathway [92] Diabetic depression Promoting autophagy via activating BDNF/TrkB pathway [99]…”
Section: Discussionmentioning
confidence: 99%
“…HG also aggravated diabetic myocardial fibrosis by increasing the expression levels of type III collagen, MMP-8, MMP-13 and MMP-14 in the diabetic myocardium and inhibited autophagy by downregulating the expression levels of autophagy-related proteins including Atg5, Atg16L1 and Beclin1 in HGinduced H9C2. Meanwhile, exogenous H 2 S could reverse the above changes, indicating that exogenous H 2 S could improve diabetic myocardial fibrosis, inhibit myocardial cell senescence and promote autophagy in diabetes models [66]. In addition, it has been reported that the upregulation of autophagy inhibited myocardial cell senescence [67].…”
Section: Exogenous H 2 S Plays An Important Role By Regulating Autophagy In Diabetic Cardiomyopathymentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, a previous study reports that NaHS can effectively reduce CF by inhibiting the expression of Ang II-induced motilin, connective tissue growth factor and type I collagen, as well as the expression of heme oxygenase-1 in cardiac fibroblasts, a process associated with the reduction of the NOX4-ROS-ERK1/2 signal transduction axis [ 146 ]. Recent studies further reveal that treatment with NaHS can markedly improve CF in diabetic rats by promoting CSE synthesis and autophagy through stimulation of the SIRT-6/AMPK and PI3K/AKT/eNOS pathways [ 147 , 148 ]. Similarly, in a thyroxine-induced CF rat model, H 2 S induces a protective effect by regulating autophagy via activation of the PI3K/AKT pathway [ 149 ].…”
Section: H 2 S and Cvdsmentioning
confidence: 99%
“…The inhibitor of AMPK was used to assess the mechanism of polydatin on the C28/I2 cells. The C28/I2 cells were divided into four groups: control (only DMEM/F-12), LPS (DMEM/F-12 contain 5 μg/mL LPS, incubate for 24 h), LPS+polydatin (DMEM/F-12 contain 5 μg/mL LPS and 1 μM polydatin, incubate for 24 h), and LPS+polydatin+Dorsomorphin 2HCl (After treated with 10 μM Dorsomorphin 2HCl for 1 h, C28/I2 cells were cultured in DMEM/F-12 with 5 μg/mL LPS and 1 μM polydatin for 24 h) [15]. Then, the role of Dorsomorphin 2HCl on the proliferation and apoptosis of C28/I2 cells and the mechanism were also detected according to the above description.…”
Section: Effect Of Dorsomorphin 2hcl On C28/i2 Cellsmentioning
confidence: 99%